Expanding the use of primaquine for the radical cure of Plasmodium vivax - Price, RN; Douglas, NM (Oxford University Press, 2018)
There is currently strong impetus for global malaria eradication with many National Malaria Control Programs setting ambitious elimination targets. Whilst intensified malaria control efforts have reduced the burden of falciparum malaria significantly, the fragile gains made thus far remain vulnerable to the threat of emergence and spread of multidrug resistant parasites. Outside of Sub-Saharan Africa, the decline in falciparum malaria has also been shadowed by a rise in the proportion of malaria due to P. vivax, which is now the predominant cause of malaria in these regions. Vivax malaria is more difficult to eradicate than P. falciparum because it can form dormant liver stages (hypnozoites) that reactivate periodically, causing recurrent infections (relapses) and further transmission.